Consequences of hydroxyapatite doping using plasma spray to implant biomaterials - Amrinder Mehta; Gurbhej Singh (Journal of Electrochemical Science and Engineering, 2023)
Hydroxyapatite (HAp) is still one of the most common bioactive coatings used on metal implants in orthopaedics due to its biocompatibility. The application of HAp to metallic implants can be accomplished using a variety of processes. Plasma spray (PS) coating stands out as the method of choice due to its dependability, affordability, and ability to protect metal surfaces against rust and wear. The use of HAp in medicine has been limited due to the material's unfavorable mechanical characteristics, such as brittleness, a lack of fracture toughness, and inadequate tensile strength. In addition, the remodeling durations of HAp-covered implants are significantly longer, the rate of osseointegration is significantly lower, and no antimicrobial actions or features are present in these implants. The mechanical and biological properties of HAp have been improved by applying various approaches, all of which fall under the category of surface modification tactics. Dopants are one of those strategies that are extremely successful at changing the characteristics and using them in HAp is one of those methods. As a result, this review study aims to consolidate data on implant Hap coating using the plasma spray approach and assess the benefits and problems associated with employing this method. In addition, the paper addresses how altering the structural, chemical, and mechanical features of HAp can assist in overcoming these limitations. In conclusion, it explains how the incorporation of entering the HAp structure can change the features that, when coated using the plasma spraying approach, alter the functionality of the implant.